The Analysis of Grammatical Errors in University Students’ Essays - Dewa Putu Ramendra; Putu Adi Krisna Juniarta; Ida Bagus Putrayasa (Jurnal Pendidikan dan Pengajaran, 2021)
This study aims to identify and analyze grammatical errors in student essays. In this case, every student's grammatical error consisting of errors in the use of diction, syntactic structure and meaning were identified and described in detail within the framework of the correct grammatical rules. This research was conducted using a qualitative descriptive method because the data collected was in the form of language use, especially grammatical errors. The subject of this research is English Education Study Program students who joined essay writing courses. Meanwhile, the object of research was grammatical errors in student essays. The data were collected through the collection of student essays obtained from the end-of-semester test and interview guide. The percentage of grammatical errors made by students in their essays in sequence were as follows; fragments: 280 (17.5%), runs on: 235 (14.7%), verb forms and verb tense: 225 (14.1%), passive: 220 (13.8%), linking verb deletion: 160 (10 %), plural disagreement: 120 (7.5%), unclear reference: 115 (7.2%), proposition misuse 89: (5.6%), subject-verb disagreement: 80 (5%), and parallelism: 74 (4.6%). Grammatical errors that needed to be considered more seriously were parallelism and passivity, which, although they look low in percentage terms, for they were rarely used in student essays; but when both forms were present, the grammatical construction tended to be wrong. In addition, both forms were also difficult to understand, compared to other types of errors that could be learned quickly